Functional architecture and cell wall composition of peltate scales involved in leaf water absorption - dos Santos, Maria Eduarda; de Lima, Jéssica Ferreira; de Oliveira, Denis Coelho; Moreira, Ana Silvia Franco Pinheiro (Frontiers in Plant Science, 2026)
IntroductionFoliar water uptake (FWU) is a mechanism that contributes to plant water balance, especially in epiphytic environments. Morphological features such as the presence of peltate scales in bromeliads are adaptive traits for FWU. In this study, we investigated which structural and chemical variations in the walls of these trichomes are related to FWU. To address this, we used Tillandsia loliacea Mart. ex Schult. & Schult.f., Tillandsia pohliana Mez, and Tillandsia recurvata (L.) L. (Bromeliaceae) to (i) describe the histochemical and immunocytochemical features of the peltate scales; (ii) verify whether the density and shape of the scales affect the maximum foliar water uptake capacity and the water absorption rate; and (iii) investigate whether water availability in the leaf tissue (relative water content, RWC) influences FWU in these species.MethodsCytological, histological, leaf water balance traits and immunocytochemical analyses were combined with FWU measurements.ResultsWe showed that the scales of the three study species exhibit similar structures, including total area and central disc area, but differ in shape.Pectins, hemicelluloses, and proteins were found at the junctions between the periclinal and anticlinal walls of the dome and basal cells, which correspond to the points where the scales attach to the ordinary epidermal cells. Lignin was present in the periclinal wall of the leaf epidermis, as were lipids; however, the latter were found only in the outer periclinal wall and extended along the anticlinal walls of the basal cells. Species with more irregularly shaped central discs and lower relative water content absorbed more water through their leaves.DiscussionWhile some models suggest pathways for water entry via the scales, in this work we show histochemical features and water balance traits that may favor FWU, an important foliar trait in bromeliads.